CRISPR activation identifies a novel miR-2861 binding site that facilitates the osteogenesis of human mesenchymal stem cells - Seong-Ho Park; Jungwoo Kim; Hee-Jin Yang; Ju Yeon Lee; Chi Heon Kim; Junho K. Hur; Sung Bae Park (Journal of Orthopaedic Surgery and Research)
Abstract We investigated the regulation of histone deacetylases (HDACs) by miR-2861 in the osteoblastic differentiation of human mesenchymal stem cells (MSCs) and miR-2861 binding site by CRISPR activation (CRISPRa). Transfection of miR-2861 into human MSCs was performed and the effect on osteoblast differentiation was analyzed. Using catalytically inactive Cas12a, the CRISPRa system induced targeted overexpression of endogenous miRNA and repressed the luciferase activities of reporters that contained functional miRNA target sites. The delivery of miR-2861 into MSCs enhanced osteoblast differentiation by decreased expressions of the HDAC1, 4 and 5 genes. The mechanism of HDAC5 repression by miR-2861 in humans has not been fully elucidated. To this end, the HDAC5 mRNA sequence was analyzed and a putative primate-specific miR-2861 binding site was identified in the 3’ untranslated region (3’-UTR). CRISPRa was applied to validate the putative binding site and an increase in endogenous miR-2861 was found to repress the expression of a reporter that contained the novel miR-2861 binding site. The delivery of miR-2861 to human MSCs enhanced osteoblast differentiation. In the 3’-UTR, the HDAC5 repression was mediated by the miR-2861 binding site, and miR-2861 promoted osteoblast differentiation via the inhibition of HDAC5 through a primate-specific miRNA binding site. Therefore, miRNAmiR-2861 with the CRISPRa methods might be a good biomaterial for osteogenesis augmentation.